The Influence of Psychological Empowerment and Organizational Culture on Employee Satisfaction - Usep Deden Suherman; Eeng Ahman (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2021)
ABSTRACT                This study aims to determine and analyze the influence of psychological empowerment and organizational culture on job satisfaction of employees of PT. BRI Syariah Bandung City both partially and together.               This research uses descriptive as well as verification methods. The study was conducted on 77 employees of PT. BRI Syariah Bandung City, Sampling is done using saturated sampling techniques. The data analysis technique used is multiple regression analysis.               The findings of this study are that psychological empowerment and organizational culture partially or jointly have an impact on employee job satisfaction. Furthermore, the determinant value obtained was 0.883, this means that psychological empowerment and organizational culture were able to explain job satisfaction worth 88.3%. Meanwhile, 11.7% was caused by other factors. Keywords: Psychological Empowerment, Organizational Culture, Job Satisfaction